Size effect in contact fatigue - Sosnovskii, L.A.; Zhmailik, V.A.; Komissarov, V.V. (Проблемы прочности, 2009)
The results of special experiments on the size effect in contact fatigue are presented. It is established that under constant contact loading conditions the durability is higher, the larger is the diameter of a tested element. The methods for estimation of contact fatigue resistance of gear wheels, which is based on the statistical model for a deformable solid body having a critical volume, are proposed. The limiting stresses of a gear wheel are estimated using a regulated base for this machine parts.